Risk assessment of E. coli, G. lamblia and C. parvum in raw spinach grown on Nhue River in Hanam - Kieu Thanh Truc; Luu Quoc Toan; Dang Xuan Sinh; Phuc Pham Duc; Tran Thi Tuyet Hanh; Nguyen Hung Long; Hung Nguyen-Viet (2014)
Nhue River is water spinach, consuming those raw spinach are at high risk of exposure to microbial. The purpose of this study was to assess the health risks of consuming raw water spinach contaminated by Coliforms, G. lamblia and C. parvum in Nhue River, Hanam Province. A total of 36 water spinach samples and nine water samples were collected for three types of pathogens analyses using Most Probable Number (MPN) and Immuno-fluorescent Antibodies (IFA) methods. We have assumed that 49% of fecal coliforms were E. coli and that 8% of E. coli were pathogenic. To simulate the impact of washing vegetable to remove pathogens from vegetable, water spinach were washed one, two and three times with soak in tap water. The results showed that E. coli O157:H7 in water spinach without washing, one time washing, two and three times washing reduced from 3.23 ± 1.64 to 1.42 ± 1.77 CFU/g. An average number of E. coli O157:H7 in river water were 4.77 log CFU/100ml. The mean amount of raw spinach consumption was estimated at 40.22g/person/meal, mean frequency of raw spinach consumption was 1.39 meals/person/year. The diarrhea risk associated with E. coli O157:H7 when consuming raw water spinach washed three times was 0.25; the diarrhea risks due to G. lamblia and C. parvum were 0 and 0.23, respectively. This study shows the high contamination of microbial in raw water spinach grown on Nhue River. Appropriate practices for raw water spinach preparation and consumption at the household to reduce or prevent infection risk and diarrhea risk by microbial is recommended.